DNA Methylation Differences in the Genes Responded to Photoperiod in Rice Cultivar KDML 105 - Surin Peyachoknagul; Wirat Pipatpongpinyo; Pradit Pongtongkam; Amara Thongpan; Lily Kaveeta; Poontariga Harinasut (Agriculture and Natural Resources, 2005)
Amplified Fragment Length Polymorphism (AFLP) technique was adapted using EcoRI and HpaII restriction enzymes for detection of the gene responded to photoperiod by DNA methylation in rice cultivar KDML 105. Two primer combinations, HM-G/E-AAG and HM-G/E-AGG, could generate two AFLP markers from the genomic DNA of rice cultivar KDML 105 after exposure to short day (SD) photoperiod (11 hour per day). Two AFLP markers were PG-AG and PG-GG. The PG-AG marker was found in the rice sample at 15 days after exposure to SD photoperiod and the PG-GG marker was found in those of 9,10,12 and 15 days after exposure to SD photoperiod. Both AFLP markers were cloned and subsequently sequenced. DNA sequences of PG-AG and PG-GG markers showed 98-100% similarity to the sequences of rice genomic DNA, cDNA and mRNA in the database. This indicated that PG-AG and PG-GG markers could be a part of the expressed genes and their expression might be induced or inhibited by DNA methylation mechanism under short daylength condition. The PG-AG marker is also suspected to be the gene involves in the process of flower development in rice while PG-GG marker may attribute to the process of flower induction.